A nurse-led health coaching intervention for stroke survivors and their family caregivers in hospital to home transition care in Chongqing, China: a study protocol for a randomized controlled trial - Lin, Shuanglan (Trials, 2020)
BACKGROUND: Hospital to home transition care is a most stressful period for stroke survivors and their caregivers to learn self-management of stroke-related health conditions and to engage in rehabilitation. Health coaching has been identified as a strategy to enhance self-management of poststroke care at home. However, interventions in this field that are informed by a health coaching framework are scarce. This study will address a gap in research by testing the hypothesis that a nurse-led health coaching intervention can improve health outcomes for stroke survivors and their family caregivers in hospital to home transition care. METHODS: This is a single-blind, two-arm parallel randomized controlled trial of a nurse-led health coaching program versus routine care situated in two tertiary hospitals in Chongqing, China. Stroke survivors and their primary family caregivers will be recruited together as “participant dyads”, and the estimated sample size is 140 (70 in each group). The intervention includes a 12-week nurse-led health coaching program in hospital to home transition care commencing at discharge from the hospital. The primary outcome is changes in self-efficacy of stroke survivors at 12 weeks from the baseline. The secondary outcomes are changes in stroke survivors’ and quality of life, functional ability, stroke-related knowledge, the number of adverse events, and unplanned hospital admissions, and caregivers’ self-efficacy and caregiver-related burden at 12 weeks from the baseline. The outcomes will be measured at 12 weeks and 24 weeks from the baseline. DISCUSSION: This study will examine the effect of nurse-led health coaching on hospital to home transition care for stroke survivors and their caregivers. It is anticipated that findings from this trial will provide research evidence to inform policy, and resource and practice development to improve hospital to home transition care for stroke survivors and their caregivers. TRIAL REGISTRATION: The Australian New Zealand Clinical Trials Registry (ANZCTR): ACTRN12619000321145. Registered on 1 March 2019.